Introduction to crystal growth and characterization - Benz, Klaus-Werner (Wiley, 2014)
This new textbook provides for the first time a comprehensive treatment of the basics of contemporary crystallography and crystal growth in a single volume. The reader will be familiarized with the concepts for the description of morphological and structural symmetry of crystals. The architecture of crystal structures of selected inorganic and molecular crystals is illustrated. The main crystallographic databases as data sources of crystal structures are described. Nucleation processes, their kinetics and main growth mechanism will be introduced in fundamentals of crystal growth. Some phase diagrams in the solid and liquid phases in correlation with the segregation of dopants are treated on a macro- and microscale. Fluid dynamic aspects with different types of convection in melts and solutions are discussed. Various growth techniques for semiconducting materials in connection with the use of external field (magnetic fields and microgravity) are described. Crystal characterization as the overall assessment of the grown crystal is treated in detail with respect to - crystal defects - crystal quality - field of application Introduction to Crystal Growth and Characterization is an ideal textbook written in a form readily accessible to undergraduate and graduate students of crystallography, physics, chemistry, materials science and engineering. It is also a valuable resource for all scientists concerned with crystal growth and materials engineering.